Quasi Three-Body Decay of D Meson. (April 2018) - Estabar, T.; Mehraban, H.
Abstract: The aim of this work is to provide a phenomenological analysis of the contribution of D 0 meson to K ¯ * ( 892 ) 0 π + π − ( K ¯ * ( 892 ) 0 → π + K − ), K − π + ω ( ω → π + π − π 0 ) and K − π + ø ( ø (1020) → K + K − ) quasi-three-body decays. The analysis of mentioned multi-body decays is such as to factorize into the three-body decay and several channels observed. Hadronic three-body decays receive both resonant and non-resonant contribution. Based on the factorization method, there are tree and emission annihilation diagrams for these decay modes. In the case of D 0 to vector pseudoscalar states appeared in factored terms, the matrix elements of the vector and axial vector currents between the D 0 and PV mesons can be computed by using D *+ pole. Considering the non-resonant and resonant amplitude in our computation, the theoretical values of the branching ratio are (9.78±0.46)×10 −3, (2.74±0.17)×10 −2, and (3.53±0.23)×10 −5, while the experimental results of them are (9.9±2.3)×10 −3, (2.7±0.5)×10 −2, and (4±1.7)×10 −5 respectively. Comparing computational analysis values with experimental values show that our results are in approximately agreement with them .